Public Service Media in Europe: Exploring the Relationship between Funding and Audience Performance - Saurwein, Florian; Eberwein, Tobias; Karmasin, Matthias (Javnost-The Public, 2019)
Public service media (PSM) are confronted with a continuing debate about public remits, performance, efficiency, and the public value of its offerings, and in many countries, public service organisations are put under pressure by political initiatives that question and oppose the traditional public funding models. This paper contributes to the debate about funding models and the assessment of public service media by exploring the relationship between funding (input) and audience performance (impact). Results of a comparative analysis of 17 European countries indicate that funding of PSM affects its audience performance. Broadcasters with stronger public income achieve higher market shares, stronger relevance as an information source, and greater trust in independence from external constraints. The findings underline the sensitivities around political reforms that aim at changes of PSM funding models. On the basis of the empirical analysis, the authors argue that substantial budget cuts or the abolition of public funding will probably lead to declines in audience performance—and a loss of relevance of public service media.